Current status and scope for improvement of agricultural water productivity in the Indo-Gangetic River Basin - Xueliang Cai; Sharma, Bharat R.; Matin, Mir Abdul (2010)
This paper assesses the agricultural water consumption and productivity of the predominant crop paddy rice and wheat for the Indo-Gangetic river basin (IGB) in South Asia. A new approach was adopted in the study to integrate census, remote sensing and weather data to assess crop water productivity (WP) across large scale. The average paddy field ET for rice for major growing period of June 10 to October 15 is 416 mm, which is 70% of rice potential evapotranspiration (ETp, equals to ET0*Kc). Average rice water productivity is 0.74 kg/m3. The average evapotranspiration (ETa) and WP of wheat is 299 mm and 0.94 kg/m3 respectively. Significant variations were observed for the ETa, yield and WP of rice and wheat. The scope for improvement of water productivity could be assessed by comparing ?hot? and ?bright? spots in consultation with factors such as rainfall and topography. It is found while improving yield in long term will finally lead to improved WP, reducing non-beneficial ET from low yield areas is a effective approach to improve WP in short term. Integrated land, crop and water management is the key to sustainable development of the region.